(untitled) (Wallacea Plant Protection Journal, 2025)
One of the secondary pests of stored rice is Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). Damage caused by this insect includes fungal contamination and the release of benzoquinone-containing secretions, which may pose health risks to humans. Postharvest pest control commonly relies on synthetic fumigant insecticides, yet their use is associated with environmental and health concerns. Plant-derived fumigants offer a more eco-friendly alternative. This study aimed to evaluate the fumigant effects of plant powders from lime (Citrus × aurantifolia (Christm.) Swingle) and kaffir lime leaves (Citrus hystrix DC.) on the mortality of T. castaneum adult. The experiment employed a untreated, lime leaves, kaffir lime leaves, and a combination of lime + kaffir lime leaves with five replications. Adult mortality was recorded from 3 to 30 days after treatment. Results indicated that by the final observation on day 30, treatment effects were most distinct. Lime leaves (25.67%) and kaffir lime leaves (27.44%) produced significantly higher mortality than both the untreated and the combined treatment (F₃,₁₉ = 0.83, P < 0.05). The combined treatment resulted in only 17.67% mortality, indicating no synergistic effect between the two leaves powders. Mortality in the untreated group remained below 14% throughout the experiment. Lime and kaffir lime leaves, when used individually, exhibit promising fumigant activity against T. castaneum and may serve as potential botanical alternatives for postharvest pest management.